Assessment of the relative sensitivity of the copepods Acartia tonsa and Acartia clausi exposed to sediment-derived elutriates from the Bagnoli-Coroglio industrial area. (March 2020) - Carotenuto, Ylenia; Vitiello, Valentina; Gallo, Alessandra; Libralato, Giovanni; Trifuoggi, Marco; Toscanesi, Maria; Lofrano, Giusy; Esposito, Francesco; Buttino, Isabella
Abstract: The sensitivity of the copepods Acartia tonsa, commonly used in standardized tests for environmental risk assessment and A. clausi, the dominant autochthonous congener species in the Mediterranean Sea, was assessed using sediment-derived elutriates from the industrial area of Bagnoli-Coroglio and nickel chloride as referent toxicant. Acute A. clausi naupliar immobilization test showed EC50 for elutriates E25, E56 and E84 of 23.3%, 80.5% and >100%, respectively, compared to 59.5%, 66.6% and >100% in A. tonsa . In the 7 day sublethal test, a reduction in A. clausi egg production rates was observed in all elutriates, but only in E56 for A. tonsa . Elutriate 56, which contained the highest amount of polycyclic aromatic hydrocarbons, also induced 70% mortality in A. clausi females. Although A. clausi was more sensitive than A. tonsa, the two species had convergent responses to the three elutriates, thus opening the venue for a potential use of A. clausi in standardized ecotoxicity tests. Highlights: A. clausi acute sensitivity to contaminated elutriates was higher than A. tonsa Elutriates reduced A. clausi egg production, hatching success and female survival Toxicity ranking of the elutriates was similar in the two copepod species Potential use of A. clausi in standardized ecotoxicity tests is suggested